Inclusive yet discerning : navigating worship artfully - Brown, Frank Burch, 1948- (Grand Rapids, Mich. : William B. Eerdmans Pub., 2009)
Brown combines an abiding admiration of classical idioms with an appreciation of new possibilities for the arts in worship. Interacting with a wide range of religious thinkers and leaders -- from Augustine and John Calvin to Rick Warren, Marcus Borg, and the Pope -- he addresses questions concerning "good" art and "good" music for worship. --from publisher description
Navigating worship artfully: finding a compass -- Enjoyment and discernment in the music of worship -- Singing together (with all creation): dilemmas and delights -- Is good art good for Christian worship? -- Christian music: more than just the words -- Religious music and secular music: a Calvinist perspective, re-formed -- On not giving short shrift to the arts in liturgy: the testimony of Pope Benedict XVI (Cardinal Ratzinger) -- On being beautiful and religious at the same time: reviving Plotinus.
Includes bibliographical references and index.
Keywords: Public worship; Christianity and art; Aesthetics -- Religious aspects -- Christianity; Church music; Music -- Religious aspects -- Christianity